Peranan Informasi Akuntansi Manajemen Terhadap Pengambilan Keputusan Investasi Aktiva Tetap Pada PT Samaristo Mitra Tekhnik - Fina Adistianingsih; Maria Yovita R. Pandin (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
PT Samaristo Mitra Tekhnik is a company engaged in the field of building construction services and procurement of electricity, gas and steam. PT Samaristo Mitra Tekhnik, which runs its business in the field of construction services, of course, the procurement of fixed assets greatly influences the running of the company's business. The research objective to be achieved is to determine the role of management accounting information on fixed asset investment decision making at PT Samaristo Mitra Tekhnik. This research is a qualitative descriptive research with a case study nature. The results of research conducted at PT Samaristo Mitra Tekhnik indicate that the company has implemented management accounting information in the process of making long-term decisions regarding fixed asset investments.